Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11262-015-1243-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence of Chikungunya virus plaque variants from the Comoros Island (2005)

Abstract: Chikungunya virus (CHIKV) from a human sample collected during the 2005 Chikungunya outbreak in the Comoros Island, showed distinct and reproducible large (L2) and small (S7) plaques which were characterized in this study. The parent strain and plaque variants were analysed by in vitro growth kinetics in different cell lines and their genetic similarity assessed by whole genome sequencing, comparative sequence alignment and phylogenetic analysis. In vitro growth kinetic assays showed similar growth patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In protein E3, at position 23, parental isoleucine is replaced by threonine in all strains. This mutation has also been described in Indian Ocean strains [51]. Many substitutions in the E2 protein were detected (Table 3), accompanying a major adaptive mutation in E1.…”
Section: Discussionsupporting
confidence: 63%
“…In protein E3, at position 23, parental isoleucine is replaced by threonine in all strains. This mutation has also been described in Indian Ocean strains [51]. Many substitutions in the E2 protein were detected (Table 3), accompanying a major adaptive mutation in E1.…”
Section: Discussionsupporting
confidence: 63%
“…11,12 We also observed viral variants with different plaque morphology including small plaque sizes in CHIKV primary isolate. It is curious how small plaque size variants with supposedly lower fitness were maintained in natural viral quasispecies.…”
Section: Selection Of Small Plaque Variant Of Chikvmentioning
confidence: 71%
“…15 While large plaque virus may replicate better and have higher fitness in mammalian hosts, small plaque virus may provide some selective advantage when the virus is transmitted to mosquito vector. 12 Alternating replication in mammalian host and mosquito vector provides unique selective environment and constraint for the viral quasispecies. Previously published data on another arbovirus, West Nile virus, showed that viruses from mosquitoes are more diverse than viruses from birds.…”
Section: Virulence Of Wild Type and Small Plaque Variant Of Chikvmentioning
confidence: 99%
See 1 more Smart Citation
“…2009 ), Comoros in 2005 ( Kariuki Njenga et al. 2008 ; Wasonga et al. 2015 ), India in 2008–2013 ( Abraham et al.…”
Section: Discussionmentioning
confidence: 99%